The impact of Community Share Ownership Trust on rural poverty in Tongogara rural district - Bowa, Tinashe Prosper (Midlands State University, 2017)
The research sought to establish the impact of Community Share Ownership Trust on poverty in Tongogara rural district tracing the background of poverty in Tongogara Rural District and how the Tongogara Community Share Ownership Trust have tried to address the problem. The research fulfilled set objectives which included assessing the knowledge of the Tongogara rural community about the operation of the Trust, the socio-economic benefits of the Trust as well as the sustainability question of the Trust. Relevant literatures were scrutinized linking, rejecting and supporting various views, thoughts and even theoretical analysis by various scholars around the topic under study. The researcher used the qualitative method in research and a total of 30 people participated. The researcher realized that the Trust over emphasized on the provision of social amenities like construction of schools, clinics and roads neglecting other key sectors such economic aspects and community involvement which are also vital to reduce poverty in Tongogara Rural District. The researcher recommends that poverty assessment should be done before implementing any project and these projects should be run by experts in that field not by politicians without relevant knowledge and skills.